Osadnictwo obcoplemienne i obcoetniczne w okolicach Opatowa i Sandomierza we wcześniejszym średniowieczu w świetle źródeł archeologicznych i toponomastycznych - Florek, Marek (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
By the end of the 10th century, the area of Opatów and Sandomierz was probably inhabited by a small tribe whose name has not been recorded in written sources. The establishment of a gord in Zawichost Podgórze before the end of the 9th century coupled with the emergence of a local cluster of pyre kurgan grave fields may be evidence of the arrival of new settlers from an area east of the Vistula. Inclusion of the Sandomierz area into the domain of the Wielkopolska Polans in the late 10th century resulted in disappearance of the existing tribal settlement structures which were replaced by new ones. This was related to the arrival to this area of individuals and groups representing the new Piast dynasty rule who came from other parts of the country or even from abroad. They included warriors from the ducal team, craftsmen, merchants as well as settlers relocated voluntarily or by force, possibly captives. As they represented different cultural traditions, their appearance has been well documented in archaeological sources. It also seems to be confirmed in toponymy. On top of the biggest number of Wielkopolska newcomers from the heart of the Piast dynasty domain, in the vicinity of Sandomierz and Opatów there could have also operated merchants related to the broadly defined Scandinavian and Russian culture as well as nomadic tribes, most probably Hungarians. The latter could have arrived as warriors, members of the ducal team, merchants or captives.